L08 Healthcare Needs Of Patients With Huntington's Disease In The South-east Region Of Norway. (17th September 2014) - van Walsem, MR; Howe, E; Frich, J; Andelic, N
Abstract : Introduction: Huntington's disease (HD) is a complex and progressive disease, and long-term, individually tailored multidisciplinary healthcare is important to maintain patients' functional ability and quality of life. In order to plan and improve provision of healthcare services it is essential to understand the met and unmet healthcare needs of individuals and families with HD. While previous research has described utilisation of healthcare services in HD in Europe, studies that systematically examine the health care needs of these patients are needed in order to advance our understanding. Aims: To identify met and unmet health services needs among HD patients and assess the relationship between unmet needs, functional disability, and health related quality of life. Methods: To date we included 80 patients with clinical diagnosis of HD residing in the South-East region of Norway. Measurements: Needs and Provision Complexity Scale (NPCS) (rater and patient version), a scale specifically developed to identify healthcare needs in patients with complex neurological disabilities. An algorithm is used to identify unmet healthcare needs. Additionally, the UHDRS Total Functional Capacity and Functional assessment scales and the EQ-5D a self-report measurement on quality of life scale are used. Demographic and patient characteristics are recorded. Results: We are currently analysing the collected data, and preliminary results will be presented at the conference. Conclusion: Modelling of met and unmet healthcare needs and it's relation to functional disability and quality of life across all HD disease stages may provide important information when planning appropriate long term multidisciplinary healthcare services for HD patients and families.